Variations in Calcitonin Gene-Related Peptide, Adiponectin, and Ghrelin Levels and Their Effects on Preeclampsia - Özlem Koşar Can; Umit Cabus; Cihan Kabukcu; Semin Fenkci; Veysel Fenkci; Yasar Enli (Clinical and Experimental Obstetrics & Gynecology, 2025)
Background: This study aimed to investigate serum levels of calcitonin gene-related peptide (CGRP) and explore potential associations between serum CGRP, adiponectin, and ghrelin concentrations in patients with preeclampsia. Methods: This study evaluated 43 normotensive healthy pregnant women and 36 pregnant women diagnosed with preeclampsia. Serum concentrations of CGRP, adiponectin, and ghrelin were measured in both groups during the third trimester of pregnancy. Results: Serum concentrations of CGRP were significantly elevated in the preeclampsia group compared to the control group. Conversely, the preeclampsia group exhibited significantly decreased serum levels of adiponectin and ghrelin relative to the controls. No significant correlation was observed between serum CGRP levels and adiponectin or ghrelin levels in either the preeclampsia or control groups. Conclusions: Our study demonstrates a considerable increase in serum CGRP concentrations in patients with preeclampsia compared to the control group. These outcomes strongly indicate that CGRP may play a pivotal role in the pathogenesis of preeclampsia.